FRI0516 Paquinimod (ABR-215757), an Immunomodulatory Compound, Reduces Fibrosis in the Tight Skin-1 (TSK-1) Model for Systemic Sclerosis. (10th June 2014) - Stenström, M.; Carlsson Nyhlén, H.; Nilsson, M.; Eriksson, H.; Törngren, M.; Distler, J.H.; Distler, O.; Sparre, B.; Tuvesson, H.
Abstract : Background: Paquinimod (ABR-215757), a new oral small molecular drug, belongs to the quinoline-3-carboxamide derivatives, a class of structurally related compounds (1). It targets the S100A9 protein and disrupts its binding to the pro-inflammatory receptors; Receptor for Advanced Glycation Endproducts (RAGE) and Toll-like Receptor 4, (TLR4) (2). Both RAGE and TLR4 are involved in the pathogenesis of many autoimmune and inflammatory diseases and paquinimod has shown convincing beneficial effects in several autoimmune/inflammatory disease models. Preclinical studies have shown that paquinimod affects the infiltration of myeloid cells into sites of inflammation (3). Paquinimod is in development for treatment of Systemic Sclerosis (SSc). SSc is a rare chronic autoimmune connective tissue disease characterized by excessive extracellular matrix deposition in the skin and visceral organs. Effects on several biomarkers relevant for SSc have been observed in an exploratory clinical trial of paquinimod (ClinicalTrials.gov Identifier: NCT01487551 ) in patients with SSc. Objectives: The purpose of this study was to evaluate the effects of paquinimod on skin fibrosis in the tight skin 1 (Tsk-1) mouse model, a common model for SSc. Methods: Tsk-1 mice were treated for 8 weeks, starting at the age of 7 weeks, with paquinimod ad lib. at 5 and 25 mg/kg/day or with vehicle only. The hypodermal thickness was analyzed in skin sections stained with haematoxylin and eosin. The collagen content in skin was also determined by hydroxyproline assay. Furthermore, the number of α-smooth muscle actin (αSMA) positive myofibroblasts, in the skin sections were determined by immunohistochemical staining. Total IgG levels in serum were measured by ELISA and gene expression in skin biopsies was analyzed by real-time PCR. Results: Treatment of Tsk-1 mice with paquinimod resulted in a significant (p<0.05) reduction of 24±6% (mean ± SEM) of the hypodermal thickness, a 22±6% (mean ± SEM) reduction of the hydroxyproline content, a 19±4% (mean ± SEM) decrease in the accumulation of myofibroblasts, and a 59±6% (mean ± SEM) reduction in total levels of serum IgG compared to vehicle treated mice. Paquinimod treated mice also had decreased gene expression of profibrotic biomarkers, such as Col1a2, Ccr2, Ctgf, Il-13 and Fn1 in the skin compared to vehicle treated mice. Conclusions: Our results show that paquinimod reduces development of skin fibrosis in the Tsk-1 model measured as hypodermal thickness, hydroxyproline content and number of myofibroblasts in the skin. Paquinimod treatment also resulted in a reduction in the expression of profibrotic genes in the skin. References: Jönsson et al. J Med Chem. 2004; 47:2075-88. Björk et al. PLoS Biol. 2009 Apr 28; 7(4):e97. Deronic et al. Int Immunopharmacol. 2014; 18:290-297. Disclosure of Interest: M. Stenström Shareholder of: Active Biotech., Employee of: Active Biotech., H. Carlsson Nyhlén Shareholder of: Active Biotech., Employee of: Active Biotech., M. Nilsson Shareholder of: Active Biotech., Employee of: Active Biotech., H. Eriksson Shareholder of: Active Biotech., Employee of: Active Biotech., M. Törngren Shareholder of: Active Biotech., Employee of: Active Biotech., J. Distler: None declared, O. Distler Consultant for: Active Biotech., B. Sparre Employee of: Active Biotech., H. Tuvesson Shareholder of: Active Biotech., Employee of: Active Biotech. DOI: 10.1136/annrheumdis-2014-eular.2200